INFORMATION SYSTEM OF CONSTRUCTION SERVICE WEB BASED ON PAPUA GAPEKSINDO ASSOCIATION - Mutmainna -; Sitti Nur Alam; Muhammad Riandi Widiyantoro; Salahudin Robo (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2021)
Information technology is currently growing rapidly. Computers as information technology tools play an important role in solving data processing problems. Therefore, many companies are using information technology to improve enterprise data management. One of them is GAPEKSINDO Association. It is the organization of companies in construction services. In collecting data and processing business entity data, the companies will apply for Business Certificate, Gapeksindo Association in Papua have the problems, they are data collection and data processing is still using Excel. The weakness use Excel is the data storage can be accidentally deleted and search data will take a long time. Based on the problems above, information system is needed to support Papua Gapeksindo Association in collecting data and processing business data. It can provide convenience in collecting data and processing business data, ensuring security in storing data and it will be stored in database. This information system based on web by using the Unified Modeling Language (UML) design method. The development method using the Waterfall method and the testing method using Black Box.